2011
DOI: 10.3155/1047-3289.61.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Total Fuel-Cycle Analysis of Heavy-Duty Vehicles Using Biofuels and Natural Gas-Based Alternative Fuels

Abstract: Heavy-duty vehicles (HDVs) present a growing energy and environmental concern worldwide. These vehicles rely almost entirely on diesel fuel for propulsion and create problems associated with local pollution, climate change, and energy security. Given these problems and the expected global expansion of HDVs in transportation sectors, industry and governments are pursuing biofuels and natural gas as potential alternative fuels for HDVs. Using recent lifecycle datasets, this paper evaluates the energy and emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 43 publications
(53 reference statements)
1
29
0
Order By: Relevance
“…This requires a multipollutant/multieffect air quality management strategy (Chow et al, 2010;Chow and Watson, 2011;Hidy et al, 2011;Hidy and Pennell, 2010). Transportation biofuels may reduce CO 2 emissions over their life cycles (Agusdinata et al, 2011;Hossain and Davies, 2010;Hsu et al, 2010;Meyer et al, 2011;Ou et al, 2010;Yan et al, 2010;Yu and Tao, 2009;Zhai et al, 2009), but they may result in increased gaseous and particulate pollutant emissions (Betha and Balasubramanian, 2011;Bugarski et al, 2010;Di et al, 2009; Guarieiro et al, 2009;Liu et al, 2009;Yanowitz and McCormick, 2009). Some of these emission rates may be small when engines are certified, but emission controls deteriorate over time; the more complex the after treatment, the greater is the potential for deterioration.…”
Section: Eti In Advanced Transportationmentioning
confidence: 99%
“…This requires a multipollutant/multieffect air quality management strategy (Chow et al, 2010;Chow and Watson, 2011;Hidy et al, 2011;Hidy and Pennell, 2010). Transportation biofuels may reduce CO 2 emissions over their life cycles (Agusdinata et al, 2011;Hossain and Davies, 2010;Hsu et al, 2010;Meyer et al, 2011;Ou et al, 2010;Yan et al, 2010;Yu and Tao, 2009;Zhai et al, 2009), but they may result in increased gaseous and particulate pollutant emissions (Betha and Balasubramanian, 2011;Bugarski et al, 2010;Di et al, 2009; Guarieiro et al, 2009;Liu et al, 2009;Yanowitz and McCormick, 2009). Some of these emission rates may be small when engines are certified, but emission controls deteriorate over time; the more complex the after treatment, the greater is the potential for deterioration.…”
Section: Eti In Advanced Transportationmentioning
confidence: 99%
“…Graham, Rideout, Rosenblatt, and Hendren () compared GHG emissions from trucks fueled with diesel, biodiesel, CNG, hythane (20% hydrogen, 80% CNG), and LNG, and concluded that GHG emissions varied depending on the choice of fuel, revealing that the use of natural gas only moderately improved the tailpipe emissions compared to conventional truck. Meyer, Green, Corbett, Mas, and Winebrake () conducted a comparative total fuel cycle analysis of diesel and alternative fuel (i.e., diesel and its variations, biodiesel, CNG, and LNG) HDTs, carrying 20 metric‐tons of cargo, based on the GREET model. The researchers found tailpipe emissions to be the main contributor to total GHG emissions, concluding that fuel economy and truck payload are two key variables that affect operational emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle assessment (LCA) of transportation services should include vehicle manufacturing/maintenance, infrastructure construction/rehabilitation/operation, and energy production, including supply chains (Chester and Horvath 2009). In the analysis of freight transportation, there have been only a handful of efforts to develop LCAs (Piecyk 2010;Kim and van Wee 2009), and the few studies that do exist (Strogen and Horvath 2013;Facanha 2006;Facanha and Horvath 2007;Meyer et al 2011) tend to normalize results to a comparative measure of a particular weight moved over a particular distance (e.g., tonne-kilometer [km] or ton-mile [mi]) without analyzing the effects of uni-and multimodal trips or how trips that span long distances should be addressed in environmental policy. It is important to understand trip impacts because (1) with interest in reducing freight emissions, it is not always possible (owing to market or infrastructure conditions) to shift goods from one mode to another and (2) many trips are multimodal.…”
Section: Introductionmentioning
confidence: 99%